Export productivity, finance and economic growth: Are the Southern engines of growth different? - Alessandra Guariglia; Amelia U. Santos-Paulino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Using a panel of 139 countries over the period 1992-2003, we analyse the links between export productivity, economic growth and financial development indicators. We then investigate whether the links observed in China, India and Brazil systematically differ from those observed in other countries in the sample. We find that both GDP per capita and investment generally exert a positive and significant effect on export productivity. Except for Brazil, financial development is not an important determinant of export productivity. Moreover, except for Brazil, export productivity plays a positive effect on growth, and so does financial development for both China and Brazil, but not for India. Finally, in both India and Brazil, FDI is negatively associated with growth.
Keywords: C23; F1; F23; O16; O40; O5; 330; export productivity; financial development; FDI; growth; Export; Wirtschaftswachstum; Direktinvestition; Finanzsektor; Welt